Crystalline Liquid-like Behavior: Surface-Induced Secondary Grain Growth of Photovoltaic Perovskite Thin Film - YAVUZ, İLHAN (AMER CHEMICAL SOC, 2019)
Surface effects usually become negligible on the micrometer or sub-micrometer scale due to lower surface-to-bulk ratio compared to nanomaterials. In lead halide perovskites, however, their soft nature renders them highly responsive to the external field, allowing for extended depth scale affected by the surface. Herein, by taking advantage of this unique feature of perovskites we demonstrate a methodology for property manipulation of perovskite thin films based on secondary grain growth, where tuning of the surface induces the internal property evolution of the entire perovskite film. While in conventional microelectronic techniques secondary grain growth generally involves harsh conditions such as high temperature and straining, it is easily triggered in a perovskite thin film by a simple surface post-treatment, producing enlarged grain sizes of up to 4 mu m. The resulting photovoltaic devices exhibit significantly enhanced power conversion efficiency and operational stability over a course of 1000 h and an ambient shelf stability of over 4000 h while maintaining over 90% of its original efficiency.
Keywords: BOUNDARIES; SIZE